The Impact of Overconfidence and Financial Literacy on Application-Based Investment Decisions: The Moderating Role of Religiosity - Zahrul Zima; Fitra Dharma; Retno Yuni Nur Susilowati (ROE: Research of Economics and Business, 2025)
This study aims to examine the effect of financial literacy and overconfidence on application- based investment decisions with religiosity as a moderating variable. The research method used a quantitative approach with a survey technique involving 384 respondents who are active users of digital investment applications in the Sumatra region. Data analysis was performed using Partial Least Square- Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The results showed that overconfidence had a positive and significant effect on app-based investment decisions, while financial literacy had no significant effect. Furthermore, religiosity was not found to moderate the relationship between overconfidence and financial literacy on digital investment decisions. These findings confirm that psychological factors, particularly overconfidence, are more dominant than financial literacy and religious values in influencing digital investment behavior. The implication of this study is the need for education that focuses not only on improving financial literacy but also on managing psychological biases so that investors can make more rational decisions.